Literature Review: Hand sanitizer formulation from extract and essential oil of betel leaf (Piper betle Linn.) As well as antibacterial activity test - Weri veranita; Kusumaningtyas Siwi Artini; Danang Raharjo; Ferry Effendi (LPPM Universitas Duta Bangsa Surakarta, 2021)
The pandemic encourages us to look for various ways to overcome it, from various sides, including physical mobility management, vaccine development, to drug discovery. Indonesia has long recognized and used medicinal plants as an effort to overcome health efforts. Piper betle Linn or betel is a plant known to have antiseptic properties. Traditional use is usually by boiling the betel leaf. Utilization of stew and betel leaf extract as natural antibacterial agents has advantages. This is because these plants have natural compounds that are safer than the use of drugs that contain synthetic ingredients. Research reveals that betel leaf with an extract content of more than 15% is equivalent to alcohol and ethanol content. Research and utilization of betel leaf as an antiseptic and hand sanitizer products have been done a lot, one of which is by using extracts and essential oils from betel leaves. The aim of this study was to compare the antibacterial activity of the betel leaf hand sanitizer formulation using extracts and essential oils against the tested bacteria. This research is a literature review. Information on the hand sanitizer formulation of Piper betle Linn betel leaf was collected from online databases such as Pub Med, Direct Scient, and Google Scholar.